Applying phosphorus indices at a small agricultural watershed in Southern Brazil - Josiane C. N. Waltrick; Gabriel D. Goularte; Nerilde Favaretto; Luiz C. P. Souza; Jeferson Dieckow; Volnei Pauletti; Fabiane M. Vezzani; Luciano Almeida; Jean P. G. Minella (Journal of Agriculture and Rural Development in the Tropics and Subtropics, 2018)
Best management practices at watershed scale are essential to mitigate water pollution. The objectives of this study were: (1) to estimate the P-index in a small watershed with intensive agricultural use applying five P-index versions at three scales (watershed, sub-basin and agricultural field); (2) to assess the effect of the connectivity factors (distance between the agricultural field and the stream and width of riparian native vegetation) in estimating the risk of P loss. The five P-index versions resulted in a similar risk of P loss, 75 to 83 % of the whole watershed scale (agricultural plus forest areas) was classified as low or very low risk for P loss. At the agricultural area scale, 79 to 100 % of this area was classed as high and very high risk for P loss. The low risk of P loss at watershed scale is explained by the high occurrence of forest vegetation. The reduced distance between agricultural land and streams and/or the reduced width of riparian native vegetation increased the risk of P loss. Estimated P-index values at a sub-basin scale indicated lower risk of P loss compared to agricultural field scale. In order to better estimate the risk of P loss at an agricultural field scale, we advise using a P-index which considers also connectivity factors.